Design and implementation of a pulley locking tool for air fan cooling system to enhance maintenance safety at company XYZ LNG - Mufarida, Nely Ana; Wibowo, Moch. Arif; Muarifin, Muarifin (Jurnal Polimesin, 2025)
This study addressed a critical safety and efficiency challenge in the maintenance of air fan cooling systems at company XYZ LNG, where technicians traditionally relied on unsafe manual methods, using bare hands and a wooden block to stop rotating pulleys. These practices, observed over a decade of operations, were identified as a leading cause of near-miss incidents, exposing operators to crush injuries, entanglement, and amputations. Motivated by the need for a safer, engineered solution, this research designed, fabricated, and implemented a specialized pulley locking tool. Developed through a structured engineering design process, the tool prevents direct human contact with moving components while aligning with modern safety management principles and human factors engineering. Field trials demonstrated a reduction in braking time from 20–30 minutes to only 4 minutes, along with significant ergonomic and psychological benefits reported by operators. The tool not only improved efficiency but also strengthened confidence in maintenance procedures. This work represents a practical intervention that transforms safety theory into application, providing a replicable model for other LNG facilities and industries with rotating equipment. The results highlight how engineered tools can simultaneously mitigate risks and improve productivity in high-risk environments.